1976
DOI: 10.1288/00005537-197601000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Familial laryngomalacia: A case report

Abstract: This report describes the hereditary occurrence of severe laryngomalacia in three of five siblings of a Mexican-American family. The mother, who experienced respiratory difficulties in the first year of life, may also have been affected. All three affected children required neonatal tracheostomy, and two died of pulmonary complications. Histological studies of tracheal cartilage revealed distinct hypercellularity and histochemical staining abnormalities of the cartilaginous matrix without defects in skeletal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

1981
1981
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 16 publications
0
19
0
1
Order By: Relevance
“…To date, the pathophysiology of laryngomalacia is still not fully understood and several factors may contribute to the disease [6,8]. Several anatomic changes of the supraglottis are observed in laryngomalacia [2][3][4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, the pathophysiology of laryngomalacia is still not fully understood and several factors may contribute to the disease [6,8]. Several anatomic changes of the supraglottis are observed in laryngomalacia [2][3][4].…”
Section: Discussionmentioning
confidence: 99%
“…Several anatomic changes of the supraglottis are observed in laryngomalacia [2][3][4]. Immaturity of the laryngeal cartilage has been proposed to be a contributing factor [5,6]. Increasing evidence suggests a neurologic etiology: altered sensorimotor integrative function of the larynx leads to neuromuscular hypotonia of the pharyngolaryngeal structures causing supraglottic collapse during inspiration [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histologic examination of laryngeal cartilage has not been possible in most patients with laryngomalacia because of its characteristic benign clinical course. Shulman et al performed a post-mortem evaluation of two tracheal specimens from two related individuals that suffered from a form of familial laryngomalacia that revealed some histologic abnormalities, namely hypercellularity and multiple abnormally enlarged lacunae [15]; however, since these individuals had a rare genetic laryngotracheal abnormality, we cannot use this finding as a basis to conclude that a chondropathy occurs in nonsyndromiclaryngomalacia. In fact, other histologic studies have not identified any cartilaginous abnormalities associated with laryngomalacia [13,16].…”
Section: Introductionmentioning
confidence: 99%
“…Its cause is still debated. There are many theories proposed to explain its physiopathology, such as disorders in the cartilaginous framework of the larynx and trachea, causing a greater laxity in supraglottic structures, anatomical alterations and neuromuscular immaturity [18][19][20][21] . Back in 1897, Sutherland & Lack 22 proposed an anatomical theory after studying 18 cases of congenital laryngeal obstruction, in which they concluded that the disorder was associated to the immaturity of the children cartilaginous tissue.…”
Section: Introductionmentioning
confidence: 99%